A preparation method of high temperature resistant and high thermal conductivity PPS composite material

By melt blending polyphenylene sulfide and sulfide polyarylether nitrile grafted graphene, a high-temperature and high-thermal conductivity PPS composite material is prepared, which solves the problem of difficulty in providing high-temperature and high thermal conductivity in the prior art, and achieves the improvement of the multiple properties of the material.

CN119192845BActive Publication Date: 2025-03-14DONGGUAN PUWAN PHOTOELECTRIC COOLING TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411575056.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The prior art is difficult to provide PPS composite materials with high temperature resistance and high thermal conductivity.

Method used

High temperature resistant and high thermal conductivity PPS composite material was prepared by melt blending polyphenylene sulfide and sulfide polyarylether nitrile grafted graphene. The method includes performing polycondensation reaction in a flask to produce carboxythioether polyarylethernitrile and grafting it onto the graphene surface by reaction with sulfoxide chloride and graphene oxide, and finally melt blending in a twin screw extruder.

Benefits of technology

The high high temperature resistance, thermal conductivity and mechanical properties of composite materials are improved, while the leakage resistance and thermal conductivity of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005121573890000021
    Figure BDA0005121573890000021
  • Figure BDA0005121573890000031
    Figure BDA0005121573890000031
Patent Text Reader

Abstract

The present invention relates to the technical field of polyphenylene sulfide, and discloses a preparation method of a high temperature resistant and high thermal conductivity PPS composite material, wherein 65-80 parts by weight of polyphenylene sulfide and 20-35 parts by weight of sulfide polyarylether nitrile grafted graphene are added to a twin-screw extruder, melt blended, and granulated to obtain a high temperature resistant and high thermal conductivity PPS composite material. After the graphene surface of the present invention is grafted and coated with the sulfide polyarylether nitrile molecular chain, its dispersibility is better, and the compatibility with polyphenylene sulfide is higher, and it is evenly dispersed in the polyarylether nitrile-polyphenylene sulfide alloy composite material, which plays a better reinforcing role, improves the tensile strength, flexural strength, thermal weight loss temperature, thermal conductivity of the composite material, and shows higher mechanical properties, high temperature resistance and thermal conductivity. And a higher anti-leakage tracking index CTI value is shown, with good anti-leakage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyphenylene sulfide, and in particular to a method for preparing a high-temperature resistant and high-thermal-conductivity PPS composite material. Background Art

[0002] Polyphenylene sulfide is a lightweight, high-performance polymer material that is widely used in the fields of electronics, precision machinery, and aerospace. By blending polyphenylene sulfide with high-performance resins such as polyarylethernitrile, high-density polyethylene, and polyethylene terephthalate, alloy materials with excellent performance can be obtained. Among them, polyarylethernitrile has the advantages of strong high temperature resistance, good mechanical properties, and a variety of preparation methods.

[0003] As a new type of nanomaterial, graphene has a large specific surface area, high mechanical strength, strong thermal conductivity, and good high temperature resistance. It is widely used in polymer materials such as polyphenylene sulfide, polyarylether nitrile, polyurethane, and polystyrene. Surface modification of graphene, improving its dispersibility, and improving compatibility with material matrices are research hotspots. Patent CN116462968B discloses the preparation and application of a modified graphene oxide / polyvinylidene fluoride / carboxymethyl polyphenylene sulfide composite material, in which graphene oxide is functionalized with octadecylamine, and then ultrasonically dispersed with polyvinylidene fluoride and carboxylated polyphenylene sulfide. The obtained polyphenylene sulfide composite material has higher impedance modulus and anti-corrosion properties. Compared with the invention, the present invention melt-blends polyphenylene sulfide and sulfide polyarylether nitrile grafted graphene, and the obtained composite material has higher high temperature resistance, thermal conductivity, and mechanical properties. Summary of the invention

[0004] The technical problem solved by the present invention is to provide a method for preparing a PPS composite material with high temperature resistance and high thermal conductivity.

[0005] The technical solution of the present invention is: a method for preparing a high temperature resistant and high thermal conductivity PPS composite material:

[0006] S1. Add N-methylpyrrolidone and toluene in a volume ratio of 1:(0.3-0.4) to a flask equipped with a condenser reflux tube and a water separator, add hydroquinone, 4,4'-di[3-(5-fluorobenzoic acid)]diphenyl sulfide, 2,6-dichlorobenzonitrile, and potassium carbonate in a molar ratio of 1:(0.05-0.15):(0.85-0.95):(1.8-2.2), heat to 140-150°C, reflux with water for 2-3h; then heat to 175-185°C, polycondensate for 4-6h, cool and pour the solution into water, filter and wash with water and ethanol in turn, dry and crush to obtain carboxyl sulfide polyarylether nitrile. The reaction formula is:

[0007]

[0008] S2. Add thionyl chloride and carboxyl sulfide polyarylether nitrile to a flask equipped with a condenser reflux tube, heat to 70-80°C, react for 5-8h, add the product after reduced pressure distillation to N,N-dimethylformamide, add graphene oxide and triethylamine, react at 20-30°C for 18-24h, then add water, stir for 2-4h, filter, wash with water, and dry to obtain sulfide polyarylether nitrile grafted graphene.

[0009] S3, adding 65-80 parts by weight of polyphenylene sulfide and 20-35 parts by weight of sulfide polyarylether nitrile grafted graphene into a twin-screw extruder, melt blending, and granulating to obtain a high temperature resistant and high thermal conductivity PPS composite material.

[0010] Preferably, the mass ratio of thionyl chloride, carboxyl sulfide polyarylether nitrile, graphene oxide, and triethylamine in S2 is (1200-1600):100:(5-20):(2-9).

[0011] Preferably, the preparation method of 4,4'-bis[3-(5-fluorobenzoic acid)]diphenyl sulfide is:

[0012] (1) Add toluene, ethanol, (2-2.2):1:(0.012-0.015):(3.5-4.2) 3-carboxyl-5-fluorophenylboric acid, 4,4'-dibromodiphenyl sulfide, tetrakis(triphenylphosphine)palladium, sodium carbonate; and water to a flask equipped with a condenser reflux tube, wherein the volume ratio of toluene, ethanol, and water is 1:(0.7-1):(0.6-0.8); heat to 85-100°C, react for 10-15h, stand for stratification to remove the aqueous phase, concentrate the organic phase under reduced pressure, separate by silica gel column chromatography, and the eluent is a mixed solution of ethyl acetate and petroleum ether to obtain 4,4'-di[3-(5-fluorobenzoic acid)]diphenyl sulfide. The reaction formula is as follows:

[0013]

[0014] The technical effect produced by the present invention is as follows: the present invention carries out a polycondensation reaction on hydroquinone, 2,6-dichlorobenzonitrile and 4,4'-di[3-(5-fluorobenzoic acid)]diphenyl sulfide to obtain a carboxyl sulfide polyarylether nitrile having a phenyl sulfide structural unit in the main chain and a carboxyl group in the side chain, and then reacts with thionyl chloride to generate an acyl chloride group, which reacts with a hydroxyl group on the surface of graphene oxide, thereby grafting the carboxyl sulfide polyarylether nitrile on the surface of graphene.

[0015] The carboxyl sulfide polyarylether nitrile of the invention contains a phenyl sulfide structural unit similar to polyphenylene sulfide, thereby improving the interface compatibility between the polyarylether nitrile and polyphenylene sulfide, and the two can form an alloy phase with better performance. The obtained polyarylether nitrile-polyphenylene sulfide alloy composite material has higher tensile strength and bending strength, and also has higher thermal weight loss and high temperature resistance.

[0016] After the graphene surface of the present invention is grafted and coated with sulfide polyarylethernitrile molecular chains, the graphene has better dispersibility and higher compatibility with polyphenylene sulfide, and is evenly dispersed in the polyarylethernitrile-polyphenylene sulfide alloy composite material, playing a better reinforcing role, improving the tensile strength, bending strength and thermal weight loss temperature of the composite material, showing better mechanical properties and high temperature resistance, and the graphene is evenly dispersed in the composite material to form a continuous heat conduction path, which significantly improves the thermal conductivity and thermal conductivity of the material.

[0017] The high-temperature resistant and high-thermal-conductivity PPS composite material of the present invention exhibits a relatively high CTI value and has good anti-leakage performance. DETAILED DESCRIPTION

[0018] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0019] Example 1

[0020] (1) In a flask equipped with a condenser reflux tube, 10 mL of toluene, 7 mL of ethanol, 8.8 mmol of 3-carboxy-5-fluorophenylboric acid, 4 mmol of 4,4'-dibromodiphenyl sulfide, 0.06 mmol of tetrakis(triphenylphosphine)palladium, 16.8 mmol of sodium carbonate, and 10 mL of water were added, and the mixture was heated to 100° C. and reacted for 10 h. The aqueous phase was removed by standing and stratification, and the organic phase was concentrated under reduced pressure and separated by silica gel column chromatography. The eluent was a mixed solution of ethyl acetate and petroleum ether to obtain 4,4'-bis[3-(5-fluorobenzoic acid)]diphenyl sulfide.

[0021] Example 2

[0022] (1) In a flask equipped with a reflux tube, 10 mL of toluene, 10 mL of ethanol, 8.8 mmol of 3-carboxy-5-fluorophenylboric acid, 4 mmol of 4,4'-dibromodiphenyl sulfide, 0.048 mmol of tetrakis(triphenylphosphine)palladium, 14 mmol of sodium carbonate, and 8 mL of water were added, and the mixture was heated to 85° C. and reacted for 15 h. The aqueous phase was removed by standing and stratification, and the organic phase was concentrated under reduced pressure and separated by silica gel column chromatography. The eluent was a mixed solution of ethyl acetate and petroleum ether to obtain 4,4'-bis[3-(5-fluorobenzoic acid)]diphenyl sulfide.

[0023] Example 3

[0024] (1) In a flask equipped with a condenser reflux tube and a water separator, 120 mL of N-methylpyrrolidone, 36 mL of toluene, 100 mmol of hydroquinone, 5 mmol of 4,4'-bis[3-(5-fluorobenzoic acid)]diphenyl sulfide (prepared in Example 1), 95 mmol of 2,6-dichlorobenzonitrile, and 200 mmol of potassium carbonate were added, and the mixture was heated to 150° C. and refluxed with water for 2 h; then heated to 175° C. and subjected to polycondensation reaction for 6 h. After cooling, the solution was poured into water, filtered, washed with water and ethanol in turn, dried, and crushed to obtain carboxyl sulfide polyarylether nitrile.

[0025] (2) Add 600 g of thionyl chloride and 50 g of carboxyl sulfide polyarylether nitrile to a flask equipped with a condenser reflux tube, heat to 70°C, react for 6 hours, add the product after reduced pressure distillation to 800 mL of N,N-dimethylformamide, add 2.5 g of graphene oxide and 1 g of triethylamine, react at 20°C for 24 hours, then add water, stir for 2 hours, filter, wash with water, and dry to obtain sulfide polyarylether nitrile grafted graphene.

[0026] (3) Add 800 g of polyphenylene sulfide and 200 g of sulfide polyarylether nitrile grafted graphene into a twin-screw extruder for melt blending, with the temperatures in zones 1-5 being 250° C., 290° C., 305° C., 315° C., and 320° C.; extrude and granulate to obtain a high-temperature resistant and high-thermal-conductivity PPS composite material.

[0027] Example 4

[0028] (1) In a flask equipped with a condenser reflux tube and a water separator, 120 mL of N-methylpyrrolidone, 48 mL of toluene, 100 mmol of hydroquinone, 10 mmol of 4,4'-bis[3-(5-fluorobenzoic acid)]diphenyl sulfide (prepared in Example 2), 90 mmol of 2,6-dichlorobenzonitrile, and 180 mmol of potassium carbonate were added, and the mixture was heated to 140° C. and refluxed with water for 3 h; then heated to 185° C. and subjected to polycondensation reaction for 4 h. After cooling, the solution was poured into water, filtered, washed with water and ethanol in turn, dried, and crushed to obtain carboxyl sulfide polyarylether nitrile.

[0029] (2) Add 800 g of thionyl chloride and 50 g of carboxyl sulfide polyarylether nitrile to a flask equipped with a condenser reflux tube, heat to 70°C, react for 8 hours, add the product after reduced pressure distillation to 1000 mL of N,N-dimethylformamide, add 6 g of graphene oxide and 2.8 g of triethylamine, react at 30°C for 18 hours, then add water, stir for 4 hours, filter, wash with water, and dry to obtain sulfide polyarylether nitrile grafted graphene.

[0030] (3) Add 730 g of polyphenylene sulfide and 270 g of sulfide polyarylether nitrile grafted graphene into a twin-screw extruder for melt blending, with the temperatures in zones 1-5 being 250°C, 290°C, 305°C, 315°C, and 320°C; extrude and granulate to obtain a high-temperature resistant and high-thermal-conductivity PPS composite material.

[0031] Example 5

[0032] (1) In a flask equipped with a condenser reflux tube and a water separator, 120 mL of N-methylpyrrolidone, 48 mL of toluene, 100 mmol of hydroquinone, 15 mmol of 4,4'-bis[3-(5-fluorobenzoic acid)]diphenyl sulfide (prepared in Example 1), 85 mmol of 2,6-dichlorobenzonitrile, and 220 mmol of potassium carbonate were added, and the mixture was heated to 140° C. and refluxed with water for 3 h; then heated to 180° C. and subjected to polycondensation reaction for 6 h. After cooling, the solution was poured into water, filtered, washed with water and ethanol in turn, dried, and crushed to obtain carboxyl sulfide polyarylether nitrile.

[0033] (2) Add 800 g of thionyl chloride and 50 g of carboxyl sulfide polyarylether nitrile to a flask equipped with a condenser reflux tube, heat to 80°C, react for 5 h, add the product after reduced pressure distillation to 1200 mL of N,N-dimethylformamide, add 10 g of graphene oxide and 4.5 g of triethylamine, react at 20°C for 24 h, then add water, stir for 4 h, filter, wash with water, and dry to obtain sulfide polyarylether nitrile grafted graphene.

[0034] (3) Add 650 g of polyphenylene sulfide and 350 g of sulfide polyarylether nitrile grafted graphene into a twin-screw extruder for melt blending, with the temperatures in zones 1-5 being 250° C., 290° C., 305° C., 315° C., and 320° C.; extrude and granulate to obtain a high-temperature resistant and high-thermal-conductivity PPS composite material.

[0035] Comparative Example 1

[0036] (1) Add 800 g of polyphenylene sulfide into a twin-screw extruder for melt blending, with the temperatures of zones 1-5 being 250° C., 290° C., 305° C., 315° C., and 320° C.; and extrude and granulate to obtain a PPS material.

[0037] Comparative Example 2

[0038] (1) Add 120 mL of N-methylpyrrolidone, 36 mL of toluene, 100 mmol of hydroquinone, 100 mmol of 2,6-dichlorobenzonitrile, and 200 mmol of potassium carbonate to a flask equipped with a condenser reflux tube and a water separator, heat to 150° C., and reflux with water for 2 h; then heat to 175° C. and perform polycondensation reaction for 6 h. After cooling, pour the solution into water, filter, wash with water and ethanol in turn, dry, and crush to obtain polyarylethernitrile.

[0039] (2) Add 800 g of polyphenylene sulfide and 200 g of polyarylether nitrile into a twin-screw extruder for melt blending, with the temperatures of zones 1-5 being 250° C., 290° C., 305° C., 315° C., and 320° C.; extrude and granulate to obtain a high-temperature resistant and high-thermal-conductivity PPS composite material.

[0040] Comparative Example 3

[0041] (1) 800 g of polyphenylene sulfide and 200 g of carboxyl sulfide polyarylether nitrile (prepared in Example 3) were added to a twin-screw extruder for melt blending. The temperatures in zones 1-5 were 250° C., 290° C., 305° C., 315° C., and 320° C. The mixture was extruded and granulated to obtain a high-temperature resistant and high-thermal-conductivity PPS composite material.

[0042] Comparative Example 4

[0043] (1) In a flask equipped with a condenser reflux tube and a water separator, 120 mL of N-methylpyrrolidone, 36 mL of toluene, 100 mmol of hydroquinone, 5 mmol of 4,4'-bis[3-(5-fluorobenzoic acid)]diphenyl sulfide (prepared in Example 1), 95 mmol of 2,6-dichlorobenzonitrile, and 200 mmol of potassium carbonate were added, and the mixture was heated to 150° C. and refluxed with water for 2 h; then heated to 175° C. and subjected to polycondensation reaction for 6 h. After cooling, the solution was poured into water, filtered, washed with water and ethanol in turn, dried, and crushed to obtain carboxyl sulfide polyarylether nitrile.

[0044] (2) Add 50 g of carboxyl sulfide polyarylether nitrile, 800 mL of N,N-dimethylformamide, 2.5 g of graphene oxide, and 1 g of triethylamine into a flask, stir at 20° C. for 24 h, then add water, stir for 2 h, filter, wash with water, and dry to obtain a sulfide polyarylether nitrile-graphene blend.

[0045] (3) Add 800 g of polyphenylene sulfide and 200 g of sulfide polyarylether nitrile-graphene blend into a twin-screw extruder for melt blending, with the temperatures in zones 1-5 being 250° C., 290° C., 305° C., 315° C., and 320° C.; extrude and granulate to obtain a high-temperature resistant and high-thermal-conductivity PPS composite material.

[0046] The high temperature resistant and high thermal conductivity PPS composite material was compression molded in a flat vulcanizer at 320°C and 10MPa pressure to produce a test sample.

[0047] The tensile strength was tested according to GB / T 1040.1-2018. The flexural strength was tested according to GB / T 9341-2008.

[0048] The CTI value of PPS composite materials was tested according to the IEC60112-2003 method.

[0049] The thermal conductivity of the PPS composite material was tested using a thermal conductivity tester. The sample size was a circular sample with a thickness of 1 mm and a diameter of 12 mm. Each group of samples was tested 5 times and the average value was taken.

[0050] The thermal properties of the PPS composite material were analyzed using a thermogravimetric analyzer in a nitrogen atmosphere with a heating rate of 10°C / min and a test temperature of 25-800°C.

[0051] Table 1

[0052] Tensile strength(MPa) Bending strength(MPa) CTI value (V) Example 3 98.2 178.7 143 Example 4 116.3 213.5 137 Example 5 127.4 202.8 131 Comparative Example 1 63.8 121.6 136 Comparative Example 2 67.2 114.0 129 Comparative Example 3 81.7 147.9 134 Comparative Example 4 87.5 161.6 141

[0053] Table 2

[0054] <![CDATA[Thermal conductivity (W·m -1 K -1 )]]> <![CDATA[T 5% (℃)]]> <![CDATA[T 10% (℃)]]> Example 3 0.377 483.2 514.2 Example 4 0.529 487.5 517.6 Example 5 0.624 489.5 520.0 Comparative Example 1 0.233 474.9 502.3 Comparative Example 2 0.230 476.7 506.4 Comparative Example 3 0.239 479.8 510.3 Comparative Example 4 0.316 481.5 512.1

[0055] The PPS material of Comparative Example 1 has a tensile strength of 63.8 MPa, a tensile strength of 121.6 MPa, a CTI value of 456, and a thermal conductivity of 0.223 W·m -1 K -1 , T 5% (temperature at which the weight loss is 5%) and T 10% (Thermal weight loss 10% temperature) is 474.9°C, 502.3°C.

[0056] Compared with Comparative Example 1, Comparative Example 2 added polyarylether nitrile. Due to the poor compatibility of polyarylether nitrile with polyphenylene sulfide, the performance of polyphenylene sulfide was not well improved. The tensile strength of the composite material was only 67.2 MPa, T 5% and T 10% The increase is small, and the bending strength and CTI value have a downward trend.

[0057] Compared with Comparative Example 1, Comparative Example 3 adds carboxyl sulfide polyarylether nitrile. Since carboxyl sulfide polyarylether nitrile contains phenyl sulfide structural units similar to polyphenylene sulfide The two have good interfacial compatibility and can form an alloy phase with better performance. The obtained poly(arylether nitrile)-poly(phenylene sulfide) alloy composite material has higher tensile strength and flexural strength, and T 5% and T 10% Larger, the material has excellent high temperature resistance.

[0058] Example 3-5 The carboxyl group of carboxyl sulfide polyarylether nitrile reacts with thionyl chloride to generate an acyl chloride group, which then reacts with the hydroxyl group on the surface of graphene oxide, thereby grafting the carboxyl sulfide polyarylether nitrile on the graphene surface. After the graphene surface is grafted and coated with the sulfide polyarylether nitrile molecular chain, its dispersibility is better, and its compatibility with polyphenylene sulfide is higher. It is evenly dispersed in the polyarylether nitrile-polyphenylene sulfide alloy composite material, which plays a better reinforcing role and further improves the tensile strength, flexural strength, T of the composite material.5% and T 10% , showing better mechanical properties and high temperature resistance, and graphene is evenly dispersed in the composite material to form a continuous heat conduction path, which is beneficial to improve the thermal conductivity and thermal conductivity of the material. In addition, the composite material shows a higher CTI value, which improves the anti-leakage performance of the polyphenylene sulfide material.

[0059] Compared with Example 3, the carboxyl sulfide polyarylether nitrile of Comparative Example 4 has not been chlorinated with thionyl chloride, and cannot react with the hydroxyl groups on the surface of graphene oxide, and cannot be grafted and coated to modify graphene oxide. The graphene and carboxyl sulfide polyarylether nitrile are in a blended state, and the compatibility with polyarylether nitrile and polyphenylene sulfide is poor, and the dispersibility is not good, resulting in poor reinforcement effect of graphene, and the tensile strength, flexural strength, thermal conductivity, T of the composite material are poor. 5% and T 10% Obviously lower than Example 3.

[0060] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a high temperature resistant and high thermal conductivity PPS composite material, characterized in that: The preparation method is: S1. Add N-methylpyrrolidone, toluene, hydroquinone, 4,4'-di[3-(5-fluorobenzoic acid)]diphenyl sulfide, 2,6-dichlorobenzonitrile, and potassium carbonate into a flask equipped with a condenser reflux tube and a water separator, perform reflux with water and polycondensation reaction, and after cooling, pour the solution into water, filter, wash, dry, and crush to obtain carboxyl sulfide polyarylether nitrile; S2. Add thionyl chloride and carboxyl sulfide polyarylether nitrile to a flask equipped with a condenser reflux tube, heat to 70-80° C., react for 5-8 hours, add the product after reduced pressure distillation to N,N-dimethylformamide, add graphene oxide and triethylamine, react at 20-30° C. for 18-24 hours, then add water, stir for 2-4 hours, filter, wash, and dry to obtain sulfide polyarylether nitrile grafted graphene; S3, adding 65-80 parts by weight of polyphenylene sulfide and 20-35 parts by weight of sulfide polyarylether nitrile grafted graphene into a twin-screw extruder, melt blending, and granulating to obtain a high temperature resistant and high thermal conductivity PPS composite material.

2. The method for preparing the high temperature resistant and high thermal conductivity PPS composite material according to claim 1, characterized in that: The temperature of the reflux with water in S1 is 140-150°C for 2-3 hours, and the temperature of the polycondensation reaction is 175-185°C for 4-6 hours.

3. The method for preparing the high temperature resistant and high thermal conductivity PPS composite material according to claim 1, characterized in that: The volume ratio of N-methylpyrrolidone to toluene in S1 is 1:(0.3-0.4).

4. The method for preparing the high temperature resistant and high thermal conductivity PPS composite material according to claim 1, characterized in that: The molar ratio of hydroquinone, 4,4'-bis[3-(5-fluorobenzoic acid)]diphenyl sulfide, 2,6-dichlorobenzonitrile and potassium carbonate in S1 is 1:(0.05-0.15):(0.85-0.95):(1.8-2.2).

5. The method for preparing the high temperature resistant and high thermal conductivity PPS composite material according to claim 1, characterized in that: The mass ratio of thionyl chloride, carboxyl sulfide polyarylether nitrile, graphene oxide and triethylamine in S2 is (1200-1600):100:(5-20):(2-9).

6. The method for preparing the high temperature resistant and high thermal conductivity PPS composite material according to claim 4, characterized in that: The preparation method of the 4,4'-bis[3-(5-fluorobenzoic acid)]diphenyl sulfide is: (1) Toluene, ethanol, 3-carboxy-5-fluorophenylboric acid, 4,4'-dibromodiphenyl sulfide, tetrakis(triphenylphosphine)palladium, sodium carbonate and water are added to a flask equipped with a condenser reflux tube, heated to 85-100° C., reacted for 10-15 hours, allowed to stand for stratification to remove the aqueous phase, the organic phase is concentrated under reduced pressure, and separated by silica gel column chromatography to obtain 4,4'-bis[3-(5-fluorobenzoic acid)]diphenyl sulfide.

7. The method for preparing the high temperature resistant and high thermal conductivity PPS composite material according to claim 6, characterized in that: The volume ratio of toluene, ethanol and water in (1) is 1:(0.7-1):(0.6-0.8).

8. The method for preparing the high temperature resistant and high thermal conductivity PPS composite material according to claim 6, characterized in that: The molar ratio of 3-carboxyl-5-fluorophenylboric acid, 4,4'-dibromodiphenyl sulfide, tetrakis(triphenylphosphine)palladium and sodium carbonate in (1) is (2-2.2):1:(0.012-0.015):(3.5-4.2).

Citation Information

Patent Citations

  • Preparation and application of modified graphene oxide / polyvinylidene fluoride / carboxymethyl polyphenylene sulfide composite material

    CN116462968B

  • Method for preparing polyphenylene sulfide / graphene composite material

    CN104945904A

  • Cross-linking type polyarylene ether nitrile and preparation method thereof

    CN106046361A